Averlo formato perfettamente: Borromini's first two years at the Roman Oratory. (2014) - Downes, Kerry
Abstract : St Philip Neri, founder of the Roman Oratory, died in 1595, just in time to see the completion, after twenty years, of the church of Santa Maria in Vallicella (known as the Chiesa Nuova )— except for the facade (finished c. 1607). Even before his canonization in 1622 the church was a place of pilgrimage. The community he founded inhabited a mass of miscellaneous buildings east of the church, decrepit, cramped, and acquired piecemeal over time when funds allowed. The musical 'oratories' — concerts with a sermon in the middle — also attracted many visitors, and the eponymous hall in which these events took place was inadequate. The community's rule allowed them to accept donations but not to beg or canvass for them. Nevertheless, by 1624 they were able to contemplate building a new sacristy on the west of the church and they were also buying up adjacent properties on that side. Initially most of the block was already built on, but by 1650 they owned practically all of it, and the shape of a new complex (Figs 1 and 2) was discernible from partly or wholly completed new structures.